Pengaruh Penggunaan Gadget terhadap Perkembangan Karakter Peduli Sosial pada Anak Usia 4-5 Tahun di Taman Kanak-Kanak Adetia - Nanda Yuliantika; Humaidah Br. Hasibuan; Raisah Armayanti Nasution (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research is quantitative research and an ex-post-facto approach, this research involves collecting data through questionnaires aimed at parents and direct observation of young children. The population numbered 15 children. So the formulation of the problem in this research is "How do gadget users develop the social care character of children aged 4-5 years in Adetia Kindergarten? How does the social care character of children aged 4-5 years in Adetia Kindergarten develop? What is the influence of gadget use on development of the social care character of children aged 4-5 years at Adetia Kindergarten?". This research aims to examine the influence of gadget use on the development of social care character in children aged 4-5 years at Adetia Kindergarten. The data analysis technique used in this research is using data collection techniques by distributing questionnaires to respondents. The observation sheet is used as an observation sheet to see the influence of gadget use on the development of the social care character of children aged 4-5 years at Adetia Bandar Setia Kindergarten. The results of the research and tests carried out show that the rxy result is 1.87. Then proceed by looking at the r table, the value of the "r" product moment coefficient of 15 with a significance level of 5% is 0.514, which means it is greater than the r table, namely 1.87 ≥ 0.514. This figure shows that the working hypothesis (Ha) in this study is accepted, namely that there is an influence of gadget use on the development of the social care character of early childhood 4-5 years old at Adetia Kindergarten.